JURIDICAL ANALYSIS OF CONTRIBUTION IMPLEMENTATION APBD (REGIONAL EXPENDITURE REVENUE BUDGET) REGARDING AID RECIPIENTS IN THE PROGRAMNATIONAL HEALTH INSURANCE (STUDY ON BPJS KESEHATAN, NORTH ACEH DISTRICT) - Hasnur Ferya Khomaini; Bambang Fitrianto; Dahlan; Andry Syafrizal Tnjung (Journal of International Islamic Law, Human Right and Public Policy, 2024)
Article 409 paragraph (4) of Law Number 17 of 2023 concerning Health states that the Regional Government allocates the Health budget from the APBD in accordance with regional Health needs. However, the budget allocation still includes expenditure for health sector personnel, not fully for promotive, preventive, curative and rehabilitative purposes. In North Aceh Regency, the APBD allocation for PBI is crucial in ensuring the sustainability and success of the JKN program, especially in the long term. To find out the legal arrangements for APBD contributions to Recipients of Contribution Assistance (PBI) in the National Health Insurance (JKN) program, the implementation of APBD contributions to Recipients of Contribution Assistance (PBI) in the National Health Insurance (JKN) program in Kab. North Aceh, and obstacles and solutions to the implementation of APBD contributions for Contribution Assistance Recipients (PBI) in the National Health Insurance (JKN) program in the District. North Aceh. The research method used is normative legal research through library research or document study. This research also uses an empirical/sociological juridical approach through field studies. The research results show that the legal regulation of Regional Revenue and Expenditure Budget (APBD) contributions for Contribution Assistance Recipients (PBI) in the National Health Insurance Program (JKN) is an important part of the government's efforts to realize universal health coverage in Indonesia. Implementation of Regional Revenue and Expenditure Budget (APBD) contributions for Contribution Assistance Recipients (PBI) in the National Health Insurance Program (JKN) in North Aceh Regency is a crucial component in the regional government's efforts to guarantee access to health services for all its citizens, especially those in the community unable. Even though it is faced with various obstacles such as budget limitations, difficulties in identifying and verifying beneficiaries, challenges in inter-agency coordination, as well as administrative and bureaucratic complications, North Aceh District is trying to optimize the use of APBD funds to support the sustainability and effectiveness of the JKN program. Obstacles in implementing Regional Revenue and Expenditure Budget (APBD) contributions to Recipients of Contribution Assistance (PBI) in the National Health Insurance Program (JKN) in North Aceh Regency include budget limitations, difficulties in identifying and verifying beneficiaries, challenges in coordination between institutions, as well as complications administration and bureaucracy. Solutions to overcome these obstacles involve optimizing regional financial resources, using information technology to update and verify beneficiary data efficiently, increasing coordination and communication between institutions through the establishment of coordination forums, as well as reforming administrative and bureaucratic procedures to speed up the process of allocation and distribution of funds.